Automatic Pet Feeder Using Internet Of Things (Iot) Technology - Nor Alia Maisarah, Hamzan (2023)
Nowadays, people of this era have developed a lifestyle of keeping pets. This is due to the fact that keeping pets may relieve tension and boredom at home, especially for individuals who are alone at home. However, people nowadays are preoccupied with their busy schedules, employment and always travel on vacations. As a result, the owner worries about the pet at home. In this project, the automatic pet feeder using Internet of Things (IoT) technology with mobile application is developed to help the pet owner. The rapid application development (RAD) method was determined to be the best appropriate technique for this suggested project. In comparison to other software development models, the RAD model is the most appropriate methodology for planning, structuring, and developing this system. This is because the RAD model can speed up the development of an automatic pet feeder system. The automatic pet feeder will have connected with the WIFI connection at home. By using this system, the owner of the pet can monitor their pet using the mobile application. Through the mobile application, the owner can check on their pet's situation in the actual time by using camera that attach in the hardware device, can schedule the feeding time based on preferable weight. There is also a sound that attached to attract the pet come near to the devices. This project can help a lots of pet owner to taking care of their pet while they are away from home. Other than that, their pets will get enough food and not excess which will be harmful to their pets' health. This system also can be used to feed others pets such as cats, dogs, and rabbits, as well as fish inside the aquarium. As a result, the primary goal of this project is to ensure that the adorable pet receives their food on time, allowing the pet owner to focus on their work without feeling worried about their pet’s nutrient requirements.